Job crafting and employees' general health: the role of work-nonwork facilitation and perceived boundary control - Yanwei Shi; Dan Li; Nan Zhang; Ping Jiang; Deng Yuling; Julan Xie; Jun Yang (BMC, 2022)
Abstract Background Job crafting is associated with positive work-related outcomes, but its effects on nonwork-related outcomes are unclear. The conservation of resources theory informed the hypotheses that work-nonwork facilitation mediates the relationship between job crafting and general health, and this mediation process is moderated by perceived boundary control. Methods Using a two-wave design, 383 employees from a range of work settings completed questionnaires in which they rated job crafting, work-nonwork facilitation, general health and perceived boundary control. Results Moderated mediation analysis showed that work-nonwork facilitation mediated the relationship between job crafting and employee general health. Further, perceived boundary control moderated this indirect effect, such that the indirect effect was stronger for employees with high perceived boundary control than those with low perceived boundary control. Conclusions This study is an important step forward in understanding the effect of job crafting on nonwork domains, and in clarifying "how" and "when" job crafting might affect employees' general health. Further, the results have practical implications for fostering employee general health.